LITERATUR REVIEW: IMPLEMENTASI PEMBELAJARAN BERBASIS TUGAS (TASK BASED LEARNING) DALAM DOKUMENTASI ASUHAN KEBIDANAN: Array (LPPM STIKes Buleleng, 2019)
Writing skills is one of the skills that must be mastered by a midwife in documenting midwifery care. Therefore in learning to document midwifery care an effective learning model is needed so that students are able to develop their writing skills. This study aims to analyze articles related to task-based learning models. The design used is a review literature that is collecting articles related to the task-based learning model. The results of the study show that task-based learning has advantages because it is one of the excellent learning models in developing a variety of basic skills that students must possess including thinking skills, decision-making skills, creativity skills, problem solving skills, and at the same time being considered effective for developing self-confidence and self-management of students. With this learning model, it is expected to be able to help students stimulate their knowledge and sensitivity to be conveyed through writing. Keywords: Task Based Learning, Midwifery Care Documentation Skills